Determination of Internal Auditor Performance with Job Satisfaction as a Mediator at Muhammadiyah Universities throughout Indonesia - Safier Ramdani; Tri Widyastuti; Darmansyah Darmansyah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the influence of leadership style, professionalism, locus of control (LOC), and independence on the performance of internal auditors at Muhammadiyah and Aisyiyah Higher Education Institutions (PTM/A) in Indonesia, with job satisfaction as a mediating variable. The study uses an explanatory quantitative approach with a sample of 101 internal auditors selected through purposive sampling from various PTM/A across Indonesia. Data was analyzed using Structural Equation Model-Partial Least Square (SEM-PLS). The results indicate that leadership style and professionalism have a significant positive effect on both internal auditor performance and job satisfaction. However, locus of control and independence did not show a significant effect on auditor performance. Job satisfaction was found to effectively mediate the influence of leadership style and professionalism on performance, but did not mediate the influence of locus of control and independence. The research model demonstrates a very strong explanatory power, with R² values of 98.7% for job satisfaction and 62.7% for auditor performance. This study makes a significant contribution to the internal audit literature and provides a strategic foundation for institutions to strengthen leadership and professional ethics to improve organizational governance quality.